Evaluation of Preparatory Classes (CPGE) Final Written Examinations According to Bloom’s Taxonomy - Chana, Si Mohamed; Yamina EL Kirat El Allame; Karima Belghiti (International Journal of Language and Literary Studies, 2021)
Moroccan students at all levels are required to sit for standardized exams every academic year. Being summative rather than formative, these exams serve certain educational purposes: evaluate students’ linguistic and/ or cognitive competencies. Students in preparatory classes (henceforth CPGE) are no exception; they are required to sit for a national exam every year before they can join any school of engineering or business. Because developing students’ critical thinking abilities is a prerequisite in the CPGE guidelines, the written national exams are supposedly designed to assess students’ critical thinking skills. The present study aims to evaluate CPGE national exams; that is, to examine the extent to which these exams assess students’ critical thinking according to Bloom’s taxonomy. Accordingly, this paper adopts a mixed-method approach to analyze and evaluate all CPGE exams since 2012. The study revealed that teachers have controversial views about the objective of national exams; it also showed that all the exams’ questions do not equally assess students’ different levels of critical thinking skills. This pushed teachers to suggest some measures to improve CPGE national exams.